A highly accurate, low cost test forBRCA1 mutations. Issue 10 (1st October 1999) - van Orsouw, Nathalie J; Dhanda, Rahul K; Elhaji, Youssef; Narod, Steven A; Li, Frederick P; Eng, Charis; Vijg, Jan
Abstract : The hereditary breast and ovarian cancer syndrome is associated with a high frequency of BRCA1 mutations. However, the widespread use of BRCA1 testing has been limited to date by three principal concerns: the fear of loss of health and life insurance, the uncertain clinical value of a positive test result, and the current lack of an inexpensive and sensitive screening test for BRCA1 mutations. We have developed an inexpensive system for gene mutational scanning, based on a combination of extensive multiplex PCR amplification and two dimensional electrophoresis. The efficiency of this system, as a screening test for BRCA1 mutations, was evaluated in a panel of 60 samples from high risk women, 14 of which contained a previously identified mutation in BRCA1 . All 14 mutations were identified, as well as an additional five that had previously escaped detection. In addition to the 19 mutations, a total of 15 different polymorphic variants were scored, most of which were recurring. All were confirmed by nucleotide sequencing. The cost of screening per sample was calculated to be approximately US70 for the manual technique used in this study, and may be reduced to approximately US10 with the introduction of commercially available PCR robotics and fluorescent imaging. Implementation of this method of mutation screening in the research and clinical setting should permit rapid accrual of quantitative data on genotype-phenotype associations for the evaluation of diagnostic testing.